2015
DOI: 10.1242/dev.120535
|View full text |Cite
|
Sign up to set email alerts
|

The SynCAM synaptic cell adhesion molecules are involved in sensory axon pathfinding by regulating axon-axon contacts

Abstract: Synaptic cell adhesion molecules (SynCAMs) are crucial for synapse formation and plasticity. However, we have previously demonstrated that SynCAMs are also required during earlier stages of neural circuit formation because SynCAM1 and SynCAM2 (also known as CADM1 and CADM2, respectively) are important for the guidance of post-crossing commissural axons. In contrast to the exclusively homophilic cis-interactions reported by previous studies, our previous in vivo results suggested the existence of heterophilic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 19 publications
2
21
0
1
Order By: Relevance
“…Initially, it was reported that SynCAMs would preferentially form cis-homodimers which would interact homo-and heterophilically with dimers in trans (Takai et al, 2008;Fogel et al, 2007). It is clear now that the interaction pattern is even more complex and cis-heterodimers are clearly formed Fogel et al, 2011;Frei et al, 2014). Furthermore, the composition of cis-dimers determines the affinities for trans-interactions, similar to what was found previously for other IgSF CAMs Kunz et al, 2002).…”
Section: Syncams Go the Other Way: Inducers Of Synapsessupporting
confidence: 71%
See 4 more Smart Citations
“…Initially, it was reported that SynCAMs would preferentially form cis-homodimers which would interact homo-and heterophilically with dimers in trans (Takai et al, 2008;Fogel et al, 2007). It is clear now that the interaction pattern is even more complex and cis-heterodimers are clearly formed Fogel et al, 2011;Frei et al, 2014). Furthermore, the composition of cis-dimers determines the affinities for trans-interactions, similar to what was found previously for other IgSF CAMs Kunz et al, 2002).…”
Section: Syncams Go the Other Way: Inducers Of Synapsessupporting
confidence: 71%
“…The existence of such heterophilic cis-interactions was confirmed by in vitro binding studies (Frei et al, 2014). Furthermore, these studies indicated that the nature of the cis-interaction determined the binding partners in trans, as heterophilic cis-interactions changed the binding preferences of trans-binding SynCAMs compared to cishomodimers (Frei et al, 2014). …”
Section: Syncams As Axon Guidance Molecules In the Cnsmentioning
confidence: 89%
See 3 more Smart Citations